Nerve root block versus surgery (NERVES) for the treatment of radicular pain secondary to a prolapsed intervertebral disc herniation: study protocol for a multi-centre randomised controlled trial - Martin J. Wilby; Carolyn Hopkins; Emma Bedson; Sue Howlin; Girvan Burnside; Elizabeth J. Conroy; Dyfrig A. Hughes; Manohar Sharma; Anthony Marson; Simon R. Clark; Paula Williamson (Trials, 2018)
Abstract Background Sciatica is a common condition reported to affect over 3% of the UK population at any time and is often caused by a prolapsed intervertebral disc (PID). Although the duration and severity of symptoms can vary, pain persisting beyond 6 weeks is unlikely to recover spontaneously and may require investigation and treatment. Currently, there is no specific care pathway for sciatica in the National Health Service (NHS), and no direct comparison exists between surgical microdiscectomy and transforaminal epidural steroid injection (TFESI). The NERVES (NErve Root block VErsus Surgery) trial aims to address this by comparing clinical and cost-effectiveness of surgical microdiscectomy and TFESI to treat sciatica secondary to a PID. Methods/design A total of 163 patients were recruited from NHS out-patient clinics across the UK and randomised to either microdiscectomy or TFESI. Adult patients (aged 16–65 years) with sciatic pain endured for between 6 weeks and 12 months are eligible if their symptoms have not been improved by at least one form of conservative (non-operative) treatment and they are willing to provide consent. Patients will be excluded if they present with neurological deficit or have had previous surgery at the same level. The primary outcome is patient-reported disability measured using the Oswestry Disability Questionnaire (ODQ) score at 18 weeks post randomisation and secondary outcomes include disability and pain scales using numerical pain ratings, modified Roland-Morris and Core Outcome Measures Index at 12-weekly intervals, and patient satisfaction at 54 weeks. Cost-effectiveness and quality of life (QOL) will be assessed using the EQ-5D-5 L and self-report cost data at 12-weekly intervals and Hospital Episode Statistics (HES) data. Adverse event data will be collected. Analysis will follow the principle of intention-to-treat. Discussion NERVES is the first trial to evaluate the comparative clinical and cost-effectiveness of microdiscectomy to local anaesthetic and steroid administered via TFESI. The results of this research may facilitate the development of an evidence-based treatment strategy for patients with sciatica. Trial registration ISRCTN, ID: ISRCTN04820368. Registered on 5 June 2014. EudraCT EudraCT2014–002751-25. Registered on 8 October 2014.